2003
DOI: 10.1016/s0013-4686(02)00730-2
|View full text |Cite
|
Sign up to set email alerts
|

Lead-based systems as suitable anode materials for Li-ion batteries

Abstract: Three lead-based materials formed by PbO 2 , PbO and Pb as main phases were prepared by following different synthetic procedures and tested as anodic materials in Li-ion batteries by using potentiostatic and galvanostatic methods. While the reduction of Pb(IV) to Pb(II) takes place in a single step, that of Pb(II) to Pb is a complex process involving several steps. Both reduction reactions are irreversible. Lead, whether electrochemically or chemically formed, undergoes an electrochemical reaction with lithium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 23 publications
2
44
0
1
Order By: Relevance
“…86 Few studies of the lithiation of Pb have been reported. 28,46,95 This may be due to the relatively low specific capacity of Pb as compared to other active elements (550 mAh/g for Li 17 Pb 4 ). Nevertheless, Pb's low average voltage (∼380 mV) 28 and high volumetric capacity (1937 Ah/L for Li 17 Pb 4 ) are attractive.…”
Section: Reference 27mentioning
confidence: 99%
“…86 Few studies of the lithiation of Pb have been reported. 28,46,95 This may be due to the relatively low specific capacity of Pb as compared to other active elements (550 mAh/g for Li 17 Pb 4 ). Nevertheless, Pb's low average voltage (∼380 mV) 28 and high volumetric capacity (1937 Ah/L for Li 17 Pb 4 ) are attractive.…”
Section: Reference 27mentioning
confidence: 99%
“…This is fairly unsurprising as the intercalation process should promote the reduction of M(II) and a subsequent decrease in M-O binding energy, which destabilizes the structure. The basic scheme of the reaction of lithium with other tin/lead salts or oxides involves the formation of metallic atoms and a lithium compound [5,6,10,11]. Liu et al have suggested that the reaction with lithium destroys the Pb 3 (PO 4 ) 2 structure and results in the formation of lithium phosphate and lead particles in the electrode, according to…”
Section: Introductionmentioning
confidence: 99%
“…This reaction is interesting with a view to obtain negative electrode materials as in situ formed metallic particles can react reversibly with lithium to form the Li 4.4 Pb alloy [10,11] (or the Li 22 Sn 5 alloy [12,13] with tin phosphate) at a potential close to 0.0 V. However, the capacity of these phosphates has been shown to decline after a few cycles. Such a capacity loss can be ascribed to the formation of large lead or tin clusters during cycling that reduce the percolation paths associated to electron and lithium diffusion [14].…”
Section: Introductionmentioning
confidence: 99%
“…[94]. Because Pb-based anodes tend to degrade rapidly upon cycling (see e.g., Ref [101]), as with Sn, most studies have concentrated on decreasing particle size and dispersing them into a buffering inactive matrix. For instance, lead oxides have been investigated [101] and compared with tin oxide [102].…”
Section: Leadmentioning
confidence: 99%
“…Because Pb-based anodes tend to degrade rapidly upon cycling (see e.g., Ref [101]), as with Sn, most studies have concentrated on decreasing particle size and dispersing them into a buffering inactive matrix. For instance, lead oxides have been investigated [101] and compared with tin oxide [102]. More recently, PbO-C composites have been studied [103], as well as Pb-sandwiched nanoparticles (i.e., SiC-Pb-C core-shell1-shell2 nanoparticles) [104], but the gravimetric capacity is rather low (*200 mAh/g after 200 charge-discharge cycles) although the volumetric capacity is about twice that of graphite, at 1580 mAh/cm 3 (i.e., *60 % of the theoretical Pb volumetric capacity) after 600 cycles [104].…”
Section: Leadmentioning
confidence: 99%